Characteristics and Travel Patterns of The Society in Colomadu District, Surakarta - Putri, Aninda Diah Karunia; Hidayati, Nurul (Universitas Muhammadiyah Surakarta, 2025)
The high number of community activities in Colomadu District, Karanganyar, causes traffic congestion at times. This study seeks to examine respondents' characteristics and travel patterns in the presence or absence of enhancements to public transportation infrastructure. Primary data includes general information about respondents, their activities, and responses to existing facilities. Data were acquired by distributing Google Form questionnaire URLs both offline and online. The Miles and Huberman Method was employed during the analysis phase. The characteristic analysis revealed that the majority of respondents were female, aged 15-30 years, and from the student/university group. The most commonly owned vehicle was a motorcycle, with the primary reason of travel being school/college. The bulk of travels were school/college-related, with destinations in Surakarta, notably Banjarsari District. Gedongan had the most travel patterns, with 8 activities and 14 destination districts, whereas Tohudan had 7 destination cities/regencies. Gedongan and Gawanan had the most vehicle users, with six different types apiece. Initially, respondents used motorbikes rather than bus stops. With infrastructure upgrades, bus stops grew, while motorbikes declined. This resulted in a reduction in vehicle options from six to five, as well as a new bus stop layout, the majority of which came from Gedongan. Based on these results, it is hoped that improvements in facilities and services will occur in the future, so that there will be an increase in the use of BST.